2017
DOI: 10.1186/s12877-017-0569-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty and sarcopenia on postoperative outcomes in older patients undergoing gastrectomy surgery: a systematic review and meta-analysis

Abstract: BackgroundGastric cancer is a major health problem, and frailty and sarcopenia will affect the postoperative outcomes in older people. However, there is still no systematic review to determine the role of frailty and sarcopenia in predicting postoperative outcomes among older patients with gastric cancer who undergo gastrectomy surgery.MethodsWe searched Embase, Medline through the Ovid interface and PubMed websites to identify potential studies. All the search strategies were run on August 24, 2016. We search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 28 publications
2
84
2
6
Order By: Relevance
“…The evaluation of sarcopenia and its impact on prognosis of cancer patients has been attracting attention in clinical oncology. As shown in recent reviews and meta-analyses, compelling evidence has shown that sarcopenia, irrespective of definition, is independently associated with poor prognosis (37,38,(68)(69)(70). Considering the increase of the aged population, the proportion of patients suffering from both sarcopenia and gastric cancer will increase.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…The evaluation of sarcopenia and its impact on prognosis of cancer patients has been attracting attention in clinical oncology. As shown in recent reviews and meta-analyses, compelling evidence has shown that sarcopenia, irrespective of definition, is independently associated with poor prognosis (37,38,(68)(69)(70). Considering the increase of the aged population, the proportion of patients suffering from both sarcopenia and gastric cancer will increase.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…This further complicates the association between reduced HGS and malnutrition in an older population. Whether indicative of nutritional status or sarcopenia, low HGS has been shown to be a predictor of increased length of stay, postoperative complications and requirement for assistance at admission and at 6 months post‐discharge . It may therefore be useful in screening patients who would most benefit from multidisciplinary intervention and early discharge planning.…”
Section: Discussionmentioning
confidence: 99%
“…They were all responsible for editing and reviewing the manuscript, and all saw approved the final version. 4…”
Section: Contributorsmentioning
confidence: 99%
“…Sarcopenia, defined as a loss of muscle mass and function, is increasingly considered to be a major public health problem in the older population and in a range of clinical settings [1,2]. Indeed, the health consequences of sarcopenia include death, falls, new or prolonged hospitalizations, fractures, loss of mobility and physical function, a reduced quality of life [3][4][5][6]. Interestingly, most of these outcomes have potential direct or indirect costs, both for the patient and the society.…”
Section: Introductionmentioning
confidence: 99%